Erozija tal v slovenski Istri - Zorn, Matija (Geologija, 2009)
From the end of nineties of the 20th century, intense hydrologic and geomorphologic research is taking place in the Slovene Istria. As a part of this research also studies on soil erosion were undertaken in the period from 2005 to 2008. The field measurements were undertaken on closed 1m2 large erosion plots under three different land uses (on bare soils in an olive grove, on an overgrown meadow, in a forest), placed south of the Marezige village in the Rokava River basin. We show weekly measurements of surface erosion (interrill erosion) for the period of 13 months (the end of March 2005- the end of April 2006), as well as monthly and seasonal averages together with selected linear statistical correlations between soil erosion and weather parameters. From May 2005 to April 2006 the interrill erosion on bare soils in an olive grove with an inclination of 5.5° amounted to 9013 g/m2(90 t/ha) that corresponds to surface lowering rate of 8.5 mm/yr; on an overgrown meadow with an inclination of 9.4° it amounted to 168 g/m2 (1,68 t/ha) that corresponds to surface lowering rate of 0.16 mm/yr; and in a forestwith an inclination of 7.8° it amounted to 391 g/m2 (3,91 t/ha) and in aforest with an inclination of 21.4° it amounted to 415 g/m2 (4,15 t/ha), respectively, that corresponds to surface lowering rate of 0.4 mm/yr.
Keywords: erozija; fliš; Istra; Istria; prst (pedologija); Slovenia; Slovenija